2015
DOI: 10.1016/j.bmc.2015.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spiropiperidine hydantoins as a novel class of antimalarial agents

Abstract: Given the rise of parasite resistance to all currently used antimalarial drugs, the identification of novel chemotypes with unique mechanisms of action is of paramount importance. Since Plasmodium expresses a number of aspartic proteases necessary for its survival, we have mined antimalarial datasets for drug-like aspartic protease inhibitors. This effort led to the identification of spiropiperidine hydantoins, bearing similarity to known inhibitors of the human aspartic protease β-secretase (BACE), as new lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Moreover, studies on their potential mechanisms of action revealed that phenolic compounds and derivatives are very active as enzymes inhibitors. Examples of such enzymes inhibited by phenolic compounds and derivatives are aspartic proteases, xanthine oxidase, 1,5-lipoxygenase, α-glucosidase, glucose-6-phosphate dehydrogenase, carbonic anhydrase and glutathione- S -transferase [ 26 , 30 , 31 ]. It is noteworthy that nowadays some of the abovementioned enzymes including aspartic proteases, glutathione- S -transferase are clearly identified as potential new targets for drug discovery against malaria and several others metabolic dysfunctions of public health significance including cancer, obesity, epilepsy and gout.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, studies on their potential mechanisms of action revealed that phenolic compounds and derivatives are very active as enzymes inhibitors. Examples of such enzymes inhibited by phenolic compounds and derivatives are aspartic proteases, xanthine oxidase, 1,5-lipoxygenase, α-glucosidase, glucose-6-phosphate dehydrogenase, carbonic anhydrase and glutathione- S -transferase [ 26 , 30 , 31 ]. It is noteworthy that nowadays some of the abovementioned enzymes including aspartic proteases, glutathione- S -transferase are clearly identified as potential new targets for drug discovery against malaria and several others metabolic dysfunctions of public health significance including cancer, obesity, epilepsy and gout.…”
Section: Resultsmentioning
confidence: 99%
“…Meyers et al [ 21 ] identified spiropiperidine hydantoins as new leads for antimalarial drug discovery. Lead compound CWHM-123 (8-(5-chloro-2-hydroxybenzyl)-3-ethyl-1-isopentyl-1,3,8-triazaspiro[4.5]decane-2,4-dione) and its 4,5 dichloro analogue, CWHM-505, are potent antimalarials (IC 50 values against Plasmodium falciparum 3D7 of 0.310 μM and 0.099 μM) and the former features equivalent potency on the chloroquine-resistant Dd2 strain.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that compounds with piperidine rings [4,8,[21][22][23][24][25][26] have good selectivity and activity for the P. falciparum strain. This prompted us to assess their antiplasmodial activity against the chloroquine-sensitive 3D7 and chloroquine-resistant W2 strains of P. falciparum as well as their cytotoxic activity against HUVEC cells (Tables 3 and 4).…”
Section: The Antimalarial Activity Of Derivatives 6 and Target Compoumentioning
confidence: 99%
“…The 4-arylaminopiperidine is a structural moiety found in many alkaloids [4][5][6][7][8][9][10][11] and pharmaceutical products such as fentanyl and structurally-related analgesic opioids or H1-antihistamines agents such as bamipine [12][13][14][15][16][17] and neurokinin 1 (NK1) receptor antagonists [18][19][20]. Studies have shown that compounds with piperidine rings [4,8,[21][22][23][24][25][26] have good selectivity and activity for the P. falciparum strain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation